New technique for detecting cracked teeth and evaluating the crack depth by contrast-enhanced cone beam computed tomography: an in vitro study - Jie Zhou; Jieni Fu; Mo Xiao; Feng Qiao; Tiantian Fu; Yangyang Lv; Fei Wu; Cuicui Sun; Peng Li; Ligeng Wu (BMC, 2022)
Abstract Background Cracked teeth may cause various clinical symptoms depending on the extension depth of the crack and the subsequent bacterial infections. However, techniques to reliably determine the extension depths of cracks in teeth before treatment are lacking. The aim of this study was to develop a new technique based on contrast-enhanced cone beam computed tomography (CBCT) to improve the accuracy of crack depth evaluation in vitro. Methods We developed an in vitro artificial simulation model of cracked teeth. Pre-experimental CBCT (pre-CBCT), and micro-computed tomography (micro-CT) were first performed for all cracked teeth (n = 31). Contrast-enhanced CBCT was then performed by infiltrating the crack with ioversol under vacuum conditions. The sensitivities of pre-CBCT and contrast-enhanced CBCT for the diagnosis of cracked teeth were calculated. According to the K-means clusters, crack depths measured by micro-CT were changed into categorical variables. Bland-Altman plot and the intraclass correlation coefficient (ICC) were used to analyze the consistency of the crack depths between the pre-CBCT and contrast-enhanced CBCT, as well as the ICC between the contrast-enhanced CBCT and micro-CT. Receiver operating characteristic (ROC) curves were generated to assess the ability for predicting crack depth in the differential diagnosis using pre-CBCT and contrast-enhanced CBCT. Restricted cubic splines were also used to model the non-linear relationship between the crack depths of contrast-enhanced CBCT and micro-CT. Results The sensitivities of pre-CBCT and contrast-enhanced CBCT were 48.4%, and 67.7%, respectively. The ICC value of crack depth as measured by pre-CBCT and contrast-enhanced CBCT was 0.847 (95% confidence interval [CI] 0.380-0.960; P < 0.001). The areas under ROC curves (AUC) of pre-CBCT and contrast-enhanced CBCT were different: the AUC of pre-CBCT was 0.958 (P = 0.000, 95% CI 0.843-1.074), and the AUC of contrast-enhanced CBCT was 0.979 (P = 0.000, 95% CI 0.921-1.037), and the difference was not statistically significant (Z = − 0.707, P = 0.480). The ICC value of crack depth as measured by contrast-enhanced CBCT and micro-CT was 0.753 (95% CI 0.248-0.911; P < 0.001). Conclusion Contrast-enhanced CBCT under vacuum conditions with a contrast medium can significantly improve the crack detection rate of cracked teeth; however, it cannot measure the crack depths accurately.